Ethnobotanical survey, chemical composition, and antioxidant capacity of methanolic extract of the root bark of Annona cuneata Oliv. - Khallouki, Farid; Haubner, Roswitha; Ulrich, Cornelia; Owen, Robert (Journal of medicinal food, 2011)
The root bark of Annona cuneata Oliv. is traditionally used in the Democratic Republic of Congo to treat several debilitating conditions, such as hernia, female sterility, sexual asthenia, and parasitic infections. However, little is known about the composition of the secondary plant substances, which may contribute to these traditional medicinal effects. We conducted an ethnobotanical study and then evaluated the composition of the secondary plant substances in extracts of the root bark by using spectroscopic methods. After delipidation, the root bark was lixiviated in methanol, and components in the extract were studied by gas chromatography-mass spectometry, high-performance liquid chromatography (HPLC)-electrospray ionization-MS and nano-electrospray ionization-MS-MS. These methods identified 13 secondary plant substances (almost exclusively phenolic compounds): p-hydroxybenzaldehyde (I), vanillin (II), tyrosol (III), 3,4-dihydroxybenzaldehyde (IV), p-hydroxybenzoic acid (V), vanillyl alcohol (VI), syringaldehyde (VII), 4-hydroxy-3-methoxyphenylethanol (VIII), vanillic acid (IX), 3,4-dihydroxybenzoic acid (X), syringic acid (XI), and ferulic acid (XII), along with the phytosterol squalene (XIII). In the HPLC-based hypoxanthine/xanthine oxidase antioxidant assay system, the methanolic extract exhibited potent antioxidant capacity, with a 50% inhibitory concentration of 72 μL, equivalent to 1.38 mg/mL of raw extract. Thus, a methanol extract of A. cuneata Oliv. contained a range of polyphenolic compounds, which may be partly responsible for its known traditional medicinal effects. More detailed studies on the phytochemistry of this important plant species are therefore warranted.
Gesehen am 01.08.2022